Error Analysis Of Instagram Machine Translation In Indonesia Into English - lubis, Rafiqa zahra; Tambusai, Azhary (Lembaga Komunikasi dan Informasi Dosen, 2022)
This research focuses to analyze the translation errors on Instagram machine translation latest version with the theory of Machali. As human, we must always not expect a lot of the Instagram machine translation to provide a good translation. The accuracy of Instagram translation more important to make good translation, The research explores the analysis result by using words. the researcher conlude that Instagram machine translation cannot produce an honest translation, and human as a translator still have crucial role in translating. Based on the data by recognizing the translation error in each datum, semantic aspects are reliable to the translation results. Second datum, the researcher founds none translation error in refrential meaning, for translations error in grammatical meaning and one in contextual meaning.Keywords: Instagram Machine Translation, Semantic Aspects, Translation Error